A Unified Approach for Patterning via Frontal Photopolymerization. (31st August 2015) - Vitale, Alessandra; Hennessy, Matthew G.; Matar, Omar K.; Cabral, João T.
<x xml:space="preserve">Abstract</x> A unified patterning strategy via frontal photopolymerization (FPP) that is robust to a wide range of radical photopolymerizing systems, including thiol–ene and acrylic monomers is reported. The factors governing the spatiotemporal solidification process, including front position, profile shape, and thermal effects, are investigated and modeled theoretically, resulting in the predictive FPP patterning of polymer networks with prescribed dimensions.